Typification of names in the Sesleria juncifolia species complex (Poaceae) - Di Pietro, Romeo (Phytotaxa, 2013)
The nomenclature of the linear-leaved species of the Sesleria juncifolia complex is one of the topics of ongoing research on the taxonomy, genetic variation, and coenology of the genus Sesleria. This paper deals with the typification of five names belonging to the S. juncifolia complex that are widely used in the taxonomical and phytosociological literature. The holotype of S. juncifolia Suffren has been located. The names S. interrupta, S. juncifolia Host, and S. tenuifolia are lectotypified. A neotype is selected for S. ujhelyi. Images for all type specimens are provided, including those for members of the complex that are already validly typified (S. kalnikensis, S. albanica, S. apennina, S. calabrica).